Thermoelectric effect in single layer epitaxial graphene formed on semiconductor substrate. Simple analytical model - Alisultanov, Z.Z. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
In this paper we have investigated thermoelectric effect in the epitaxial graphene on a semiconductor substrateusing a simple model. We have obtained the expressions for static conductance and thermopower of the epitaxial graphene. The thermopower of the epitaxial graphene can be abnormally large near the edges of the semiconductor band gap.